Frequency-space domain acoustic wave simulation with the BiCGstab (ℓ) iterative method. (29th January 2016) - Du, Zengli; Liu, Jianjun; Liu, Wenge; Li, Chunhong
Abstract: The vast computational cost and memory requirements of LU decomposition are major obstacles to 3D seismic modelling in the frequency-space domain. BiCGstab ( ℓ ) is an effective bi-conjugate gradient method to solve the giant sparse linear equations, but the convergence rate is extremely low when the threshold value is set small enough. The BiCGstab ( ℓ ) iterative method was introduced into 3D numerical simulation to overcome these problems in this paper. Numerical examples have shown that the precision of the BiCGstab ( ℓ ) iterative method meets the demand of seismic modelling and the result is equivalent to that of LU decomposition. The computational cost and memory resource demands of the BiCGstab ( ℓ ) iterative method are superior to that of LU decomposition. It is an effective method of 3D seismic modelling in the frequency-space domain.